Acute effects of air pollutants on daily mortality and hospitalizations due to cardiovascular and respiratory diseases - Pothirat, Chaicharn; Chaiwong, Warawut; Liwsrisakun, Chalerm; Bumroongkit, Chaiwat; Deesomchok, Athavudh; Theerakittikul, Theerakorn; Limsukon, Atikun; Tajarernmuang, Pattraporn; Phetsuk, Nittaya (Journal of Thoracic Disease, 2019)
Background: Chiang Dao is one of the districts in Chiang Mai, Thailand facing high level of seasonal air pollution every year, the exposure of community dwellers to outdoor air pollutants 24 hours a day during seasonal smog period because of their open-air housing style, and agricultural occupational hazard. In addition, Chiang Dao hospital is the only available hospital serving the community with open-air wards; therefore we could certainly to identify the association between air pollution and mortality of hospitalized patients. Thus, the aim of this study was to determine the association between daily average seasonal air pollutants and daily mortality of hospitalized patients and community dwellers as well as emergency and hospitalization visits for serious respiratory, cardiovascular, and cerebrovascular diseases. Methods: This time series study was conducted between 1 March 2016 and 31 March 2017. The association of various air pollutant concentrations including particulate matter diameter less than 10 and 2.5 microns (PM10 and PM2.5), sulfur dioxide (SO2), nitrogen dioxide (NO2), carbon monoxide (CO), ozone (O3) and daily mortality of hospitalized patients and community dwellers as well as relationship with frequencies of serious respiratory, cardiovascular, and cerebrovascular diseases were analyzed using a general linear model with Poisson distribution. Results: Only PM2.5 was found to be associated with increased daily mortality of hospitalized patients (lag day 6, adjusted RR =1.153, 95% CI: 1.001–1.329), whereas PM10, PM2.5, NO2, and O3 were associated with increased daily non-accidental mortality of community dwellers (lag day 0–7, adjusted RR =1.006–1.040, 95% CI: 1.000–1.074). For acute serious respiratory events; PM10 and PM2.5 were associated with acute exacerbation of chronic obstructive pulmonary disease (AECOPD), while SO2, CO, and O3 were associated with emergency visits for community-acquired pneumonia (CAP). O3 was associated with emergency visits for heart failure (HF), NO2 with emergency visits for myocardial infarction (MI), and SO2 with hospitalized visits for cerebrovascular accident (CVA). Conclusions: Seasonal air pollutants were found to be associated with higher mortality among hospitalized patients and community dwellers with varying effects on severe acute respiratory, cardiovascular, and cerebrovascular diseases.